(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article investigates major points of the Boburnoma as one of the interesting source. Therefore, heritage of this classic novelty, the way of the learning features and points of the analytical and practical aspects were investigated by author. Moreover, as of the respected individual Zahiriddin Muhammad Babur got illustrated with major aspects of the person. Finally, paper points out both outcomes and shortcomings to get detailed illustration go both Boburnoma and Z.M. Babur to all around the world.